Inovasi Pembelajaran Balaghah Berbasis Problem-Based Learning (PBL) melalui Penyusunan Soal Pilihan Ganda di Perguruan Tinggi - Umam, Rochimul; Setiyawan, Agung; Tan Sri Hassan, Abd Rauf (UIN ANTASARI, 2025)
This article explores the implementation of Problem-Based Learning (PBL) in enhancing the teaching of balaghah (Arabic rhetoric) among undergraduate students. The study examines how PBL encourages active student engagement and fosters critical thinking through collaborative tasks, particularly in the design of multiple-choice questions. By shifting students from passive receivers of information to active creators of knowledge, PBL facilitates deeper comprehension of balaghah concepts. The research findings align with previous studies, demonstrating that PBL not only improves understanding but also increases retention of complex rhetorical principles. The article also discusses challenges encountered, such as varying levels of student comprehension, and proposes solutions like incorporating cooperative learning strategies. The results highlight the importance of pedagogical innovation, showing that PBL offers an effective approach to modernizing the teaching of classical disciplines such as balaghah.